Textile fabric and preparation method thereof
By chemically modifying polyester fibers and cotton fibers to form conductive composite fibers, the problem of insufficient conductivity and flexibility of existing fiber materials is solved, and efficient conductivity and structural stability is achieved, which is suitable for the application of smart textiles.
Patent Information
- Application Number
- CN202510344892.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-24
AI Technical Summary
Existing fiber materials have shortcomings in conductivity and flexibility, limiting their application potential in conductive and smart textiles.
By using polyester fibers and cotton fibers as substrates and using chemical modification methods, conductive composite fibers are formed. The specific steps include: treating the polyester fiber with sodium dodecylbenzenesulfonate and phosphoric acid, forming a negatively charged activated layer and phosphate groups, and then depositing a silver film in the silver ammonia solution, and enhancing its hydrophilicity and antioxidant properties through β-cyclodextrin modification. Cotton fibers were subjected to hydrochloric acid pretreatment and polyaniline coating to form, and a multi-dimensional conductive network was constructed by combining graphene and carbon nanotubes.
It significantly improves the conductivity and structural stability of textile fabrics while maintaining flexibility and comfort, making it suitable for use in conductive and smart textile applications.
Smart Images

Figure CN119859871A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textile materials and relates to a textile fabric and a preparation method thereof. Background Art
[0002] At present, smart textiles not only meet the basic needs of traditional textiles in terms of comfort, durability, breathability, etc., but also have a variety of additional functions such as sensing, conductivity, and antibacterial. Driven by the Internet of Things and intelligent technologies, the market demand for smart textiles continues to expand, and its research and development has become one of the important directions of the modern textile industry.
[0003] The functionalization and diversification of smart textiles have benefited greatly from the introduction of new nanomaterials. Among them, graphene is widely used in the functional modification of textiles due to its excellent electrical conductivity, thermal conductivity, high mechanical strength, chemical stability and light weight. By compounding graphene with fiber materials, textile fabrics can be effectively endowed with excellent electrical conductivity, while greatly improving their mechanical properties and durability while ensuring flexibility and comfort. In addition, the versatility of graphene also makes it possible for smart textiles to achieve multi-task integration, such as integrating multiple functions such as conductivity, heat generation, and protection.
[0004] However, although the introduction of graphene has provided new opportunities for the development of smart textiles, existing fiber materials still have many deficiencies in terms of conductivity and flexibility. Take polyester fiber as an example, it is widely used in the textile field due to its good mechanical properties, wear resistance and chemical stability, but its poor conductivity limits its application potential in conductive and smart textiles. Summary of the invention
[0005] In view of the above problems, the object of the present invention is to provide a textile fabric and a preparation method thereof. The present invention selects polyester fiber and cotton fiber as substrates, and endows them with excellent conductivity and multifunctionality through chemical modification. Polyester fiber exhibits high strength, wear resistance and chemical stability due to the synergistic effect of ester groups and benzene rings in its molecular structure, while surface hydrophobicity enhances anti-pollution and corrosion resistance. Through sodium dodecylbenzene sulfonate treatment, a negatively charged activation layer is formed on the surface of polyester fiber, and then phosphoric acid treatment is used to generate phosphate groups, which significantly improves the polarity and adsorption capacity of the fiber and provides attachment sites for the deposition of silver ions. The silver ions in the silver ammonia solution are bound to the fiber surface through electrostatic action and coordination bonds, and form a uniform conductive silver film under the action of ascorbic acid; the silver film is further modified by β-cyclodextrin to improve the hydrophilicity, antioxidant property and small molecule capture ability of polyester fiber. Cotton fiber has high chemical reactivity and flexibility due to the rich hydroxyl groups in cellulose. Its binding ability with aniline monomer is enhanced by hydrochloric acid pretreatment, and a uniform conductive polyaniline coating is formed by chemical oxidation polymerization. In addition, graphene and carbon nanotubes, as conductive reinforcing materials, synergistically construct a multidimensional conductive network through high specific surface area and one-dimensional conjugated structure. Polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are used to promote uniform dispersion, and glutaraldehyde cross-linking is used to enhance its bonding strength, thereby significantly improving the conductivity and structural stability of the composite fiber.
[0006] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a textile fabric, the method comprising: uniformly mixing 70-80 parts by mass of modified polyester fiber and 20-30 parts by mass of conductive composite fiber and weaving the mixture into the textile fabric; The preparation method of the modified polyester fiber is: S11: ultrasonically cleaning the polyester fiber with anhydrous ethanol to obtain a pretreated polyester fiber; adding sodium dodecylbenzene sulfonate to a phosphoric acid solution to obtain an activation solution, and immersing the pretreated polyester fiber in the activation solution to obtain an activated polyester fiber; S12: mixing silver nitrate, ethylenediaminetetraacetic acid and ammonia water to obtain a silver ammonia solution, immersing the activated polyester fiber in the silver ammonia solution, stirring and immersing, and then dropping an ascorbic acid solution to react to obtain a silver-plated modified polyester fiber; S13: preparing a β-cyclodextrin solution, adjusting the pH thereof with a sodium hydroxide solution to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution, and reacting to obtain the modified polyester fiber.
[0007] The preparation method of the conductive composite fiber comprises: S21: ultrasonically cleaning the cotton fiber with anhydrous ethanol and then drying it to obtain a first pretreated cotton fiber; immersing the first pretreated cotton fiber in a hydrochloric acid solution at room temperature to obtain a pretreated cotton fiber; S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing the solution in an ice water bath for later use, adding aniline monomer to the hydrochloric acid solution to obtain a monomer solution, immersing the pretreated cotton fiber in the monomer solution, stirring and then dropping the oxidant solution to obtain a polyaniline / cotton composite fiber; S23: adding polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to deionized water to obtain a dispersion base solution, and adding graphene and carbon nanotubes to obtain a modified dispersion solution; immersing the polyaniline / cotton composite fiber in a glutaraldehyde solution for activation, taking it out, washing it, and immersing it in the modified dispersion solution to react and obtain a modified polyaniline / cotton composite fiber; S24: immersing the modified polyaniline / cotton composite fiber in a dodecylbenzene sulfonic acid solution to obtain a doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution, adjusting the pH with acetic acid to obtain an antistatic impregnation solution, and immersing the doped modified fiber in the solution to obtain a conductive composite fiber.
[0008] Specifically, the preparation method of the modified polyester fiber is: S11: ultrasonically cleaning the polyester fiber with anhydrous ethanol and then drying it to obtain a pretreated polyester fiber; adding sodium dodecylbenzene sulfonate to a phosphoric acid solution to obtain an activation solution, immersing the pretreated polyester fiber in the activation solution, stirring at a constant temperature for reaction, taking out, washing, and drying to obtain an activated polyester fiber; S12: silver nitrate, ethylenediaminetetraacetic acid and ammonia water are mixed to obtain a silver ammonia solution, the activated polyester fiber is immersed in the silver ammonia solution, after the immersion is stirred at room temperature, an ascorbic acid solution is added dropwise, after the reaction is stirred, the silver-plated modified polyester fiber is washed and dried; S13: preparing a β-cyclodextrin solution, adjusting the pH thereof with a sodium hydroxide solution to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution, stirring at a constant temperature, washing, and drying to obtain the modified polyester fiber; The preparation method of the conductive composite fiber comprises: S21: ultrasonically cleaning the cotton fiber with anhydrous ethanol and then drying it to obtain a first pretreated cotton fiber; immersing the first pretreated cotton fiber in a hydrochloric acid solution at room temperature to obtain a pretreated cotton fiber; S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing the solution in an ice-water bath for later use, adding aniline monomer to the hydrochloric acid solution to obtain a monomer solution, immersing the pretreated cotton fiber in the monomer solution in an ice-water bath, adding the oxidant solution dropwise after stirring, continuing to stir for reaction, washing, and drying to obtain a polyaniline / cotton composite fiber; S23: adding graphene, carbon nanotubes and polyvinyl pyrrolidone to deionized water, and dispersing them ultrasonically in an ice-water bath to obtain a modified dispersion; immersing the polyaniline / cotton composite fiber in a glutaraldehyde solution for activation, taking it out, washing it, immersing it in the modified dispersion, stirring it at room temperature, taking it out, washing it, and drying it to obtain a modified polyaniline / cotton composite fiber; S24: immersing the modified polyaniline / cotton composite fiber in a dodecylbenzene sulfonic acid solution, washing and drying to obtain a doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution, adjusting the pH with acetic acid to obtain an antistatic impregnation solution, immersing the doped modified fiber, stirring at a constant temperature, taking out, washing, and drying to obtain a conductive composite fiber.
[0009] As a preferred technical solution of the present invention, in S11, the mass fraction of the phosphoric acid solution is 10-15wt.%, for example, it can be 10.0wt.%, 10.5wt.%, 11.0wt.%, 11.5wt.%, 12.0wt.%, 12.5wt.%, 13.0wt.%, 13.5wt.%, 14.0wt.%, 14.5wt.% or 15.0wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0010] In some optional embodiments, the dosage of sodium dodecylbenzene sulfonate in the activation solution is 0.5-1.0 g / L, for example, it can be 0.50 g / L, 0.55 g / L, 0.60 g / L, 0.65 g / L, 0.70 g / L, 0.75 g / L, 0.80 g / L, 0.85 g / L, 0.90 g / L, 0.95 g / L or 1.00 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0011] In some optional embodiments, the solid-liquid ratio of the pretreated polyester fiber to the activation solution is 1:(20-30), for example, it can be 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0012] In some optional embodiments, the temperature of the constant temperature stirring reaction is 60-65°C, for example, it can be 60.0°C, 60.5°C, 61.0°C, 61.5°C, 62.0°C, 62.5°C, 63.0°C, 63.5°C, 64.0°C, 64.5°C or 65.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] In some optional embodiments, the rotation speed of the constant temperature stirring reaction is 200-250rpm, for example, it can be 200rpm, 205rpm, 210rpm, 215rpm, 220rpm, 225rpm, 230rpm, 235rpm, 240rpm, 245rpm or 250rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] In some optional embodiments, the constant temperature stirring reaction time is 15-20 min, for example, it can be 15.0 min, 15.5 min, 16.0 min, 16.5 min, 17.0 min, 17.5 min, 18.0 min, 18.5 min, 19.0 min, 19.5 min or 20.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] As a preferred technical solution of the present invention, in S12, the concentration of silver nitrate in the silver ammonia solution is 0.1-0.2M, for example, it can be 0.10M, 0.11M, 0.12M, 0.13M, 0.14M, 0.15M, 0.16M, 0.17M, 0.18M, 0.19M or 0.20M, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In some optional embodiments, the concentration of EDTA in the silver ammonia solution is 2-3 g / L, for example, 2.0 g / L, 2.1 g / L, 2.2 g / L, 2.3 g / L, 2.4 g / L, 2.5 g / L, 2.6 g / L, 2.7 g / L, 2.8 g / L, 2.9 g / L or 3.0 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In some optional embodiments, ammonia water is added to adjust the pH of the silver ammonia solution to 9-10, for example, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9 or 10.0, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In some optional embodiments, the solid-to-liquid ratio of the activated polyester fiber to the silver ammonia solution is 1:(30-40), for example, it can be 1:30, 1:31, 1:32, 1:33, 1:34, 1:35, 1:36, 1:37, 1:38, 1:39 or 1:40, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] In some optional embodiments, the concentration of the ascorbic acid solution is 15-20 g / L, for example, it can be 15.0 g / L, 15.5 g / L, 16.0 g / L, 16.5 g / L, 17.0 g / L, 17.5 g / L, 18.0 g / L, 18.5 g / L, 19.0 g / L, 19.5 g / L or 20.0 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In some optional embodiments, the dripping speed of the ascorbic acid solution is 2-3 mL / min, for example, it can be 2.0 mL / min, 2.1 mL / min, 2.2 mL / min, 2.3 mL / min, 2.4 mL / min, 2.5 mL / min, 2.6 mL / min, 2.7 mL / min, 2.8 mL / min, 2.9 mL / min or 3.0 mL / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In some optional embodiments, the molar ratio of ascorbic acid to silver nitrate is (0.8-1):1, for example, it can be 0.80:1, 0.82:1, 0.84:1, 0.86:1, 0.88:1, 0.90:1, 0.92:1, 0.94:1, 0.96:1, 0.98:1 or 1.00:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] In some optional embodiments, the stirring reaction temperature is 20-25°C, for example, it can be 20.0°C, 20.5°C, 21.0°C, 21.5°C, 22.0°C, 22.5°C, 23.0°C, 23.5°C, 24.0°C, 24.5°C or 25.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] In some optional embodiments, the rotation speed of the stirring reaction is 150-200rpm, for example, it can be 150rpm, 155rpm, 160rpm, 165rpm, 170rpm, 175rpm, 180rpm, 185rpm, 190rpm, 195rpm or 200rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In some optional embodiments, the stirring reaction time is 20-30 min, for example, it can be 20.0 min, 21.0 min, 22.0 min, 23.0 min, 24.0 min, 25.0 min, 26.0 min, 27.0 min, 28.0 min, 29.0 min or 30.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] As a preferred technical solution of the present invention, in S13, the mass fraction of the β-cyclodextrin solution is 1-1.5wt.%, for example, it can be 1.00wt.%, 1.05wt.%, 1.10wt.%, 1.15wt.%, 1.20wt.%, 1.25wt.%, 1.30wt.%, 1.35wt.%, 1.40wt.%, 1.45wt.% or 1.50wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] In some optional embodiments, the concentration of the sodium hydroxide solution is 0.1-0.2M, for example, it can be 0.10M, 0.11M, 0.12M, 0.13M, 0.14M, 0.15M, 0.16M, 0.17M, 0.18M, 0.19M or 0.20M, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In some optional embodiments, the sodium hydroxide solution adjusts the pH of the β-cyclodextrin solution to 6-7, for example, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9 or 7.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In some optional embodiments, the solid-liquid ratio of the silver-plated modified polyester fiber to the functionalized solution is 1:(20-30), for example, it can be 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional embodiments, the constant temperature stirring temperature is 50-55°C, for example, it can be 50.0°C, 50.5°C, 51.0°C, 51.5°C, 52.0°C, 52.5°C, 53.0°C, 53.5°C, 54.0°C, 54.5°C or 55.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional embodiments, the constant temperature stirring speed is 150-200rpm, for example, it can be 150rpm, 155rpm, 160rpm, 165rpm, 170rpm, 175rpm, 180rpm, 185rpm, 190rpm, 195rpm or 200rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional embodiments, the constant temperature stirring time is 90-100 min, for example, it can be 90.0 min, 91.0 min, 92.0 min, 93.0 min, 94.0 min, 95.0 min, 96.0 min, 97.0 min, 98.0 min, 99.0 min or 100.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] As a preferred technical solution of the present invention, in S21, the solid-liquid ratio of the first pretreated cotton fiber to the hydrochloric acid solution is 1:(30-40), for example, it can be 1:30, 1:31, 1:32, 1:33, 1:34, 1:35, 1:36, 1:37, 1:38, 1:39 or 1:40, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In some optional embodiments, the concentration of the hydrochloric acid solution is 0.5-1M, for example, it can be 0.50M, 0.55M, 0.60M, 0.65M, 0.70M, 0.75M, 0.80M, 0.85M, 0.90M, 0.95M or 1.00M, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional embodiments, the first pretreated cotton fiber is immersed in the hydrochloric acid solution for 10-15 min, for example, 10.0 min, 10.5 min, 11.0 min, 11.5 min, 12.0 min, 12.5 min, 13.0 min, 13.5 min, 14.0 min, 14.5 min or 15.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] As a preferred technical solution of the present invention, in S22, the concentration of ammonium persulfate in the oxidant solution is 0.25-0.3M, for example, it can be 0.250M, 0.255M, 0.260M, 0.265M, 0.270M, 0.275M, 0.280M, 0.285M, 0.290M, 0.295M or 0.300M, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional embodiments, the concentration of aniline monomer in the monomer solution is 0.2-0.25M, for example, it can be 0.200M, 0.205M, 0.210M, 0.215M, 0.220M, 0.225M, 0.230M, 0.235M, 0.240M, 0.245M or 0.250M, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional embodiments, the solid-to-liquid ratio of the pretreated cotton fiber to the monomer solution is 1:(30-35), for example, it can be 1:30.0, 1:30.5, 1:31.0, 1:31.5, 1:32.0, 1:32.5, 1:33.0, 1:33.5, 1:34.0, 1:34.5 or 1:35.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional embodiments, the molar ratio of the aniline monomer to ammonium persulfate is 1:(1-1.25), for example, it can be 1:1.00, 1:1.025, 1:1.050, 1:1.075, 1:1.100, 1:1.125, 1:1.150, 1:1.175, 1:1.200, 1:1.225 or 1:1.250, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional embodiments, the time for continuing to stir the reaction is 3-4h, for example, it can be 3.0h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h or 4.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] As a preferred technical solution of the present invention, in S23, the mass fraction of the polyvinyl pyrrolidone is 0.8-1.2wt.%, for example, it can be 0.80wt.%, 0.85wt.%, 0.90wt.%, 0.95wt.%, 1.00wt.%, 1.05wt.%, 1.10wt.% or 1.20wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional embodiments, the mass fraction of the sodium dodecylbenzene sulfonate is 0.2-0.5wt.%; for example, it can be 0.2wt.%, 0.23wt.%, 0.26wt.%, 0.29wt.%, 0.32wt.%, 0.35wt.%, 0.38wt.%, 0.41wt.%, 0.44wt.%, 0.47wt.% or 0.5wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some optional embodiments, the mass ratio of graphene to carbon nanotubes is (1-2):1, for example, it can be 1.00:1, 1.10:1, 1.20:1, 1.30:1, 1.40:1, 1.50:1, 1.60:1, 1.70:1, 1.80:1, 1.90:1 or 2.00:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some optional embodiments, the concentration of the mixture of graphene and carbon nanotubes is 1.2-1.5 mg / mL, for example, it can be 1.20 mg / mL, 1.25 mg / mL, 1.30 mg / mL, 1.35 mg / mL, 1.40 mg / mL, 1.45 mg / mL or 1.50 mg / mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In some optional embodiments, the power of the ultrasonic dispersion is 150-200 W, for example, it can be 150 W, 155 W, 160 W, 165 W, 170 W, 175 W, 180 W, 185 W, 190 W, 195 W or 200 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some optional embodiments, the ultrasonic dispersion time is 60-65 min, for example, it can be 60 min, 60.5 min, 61 min, 61.5 min, 62 min, 62.5 min, 63 min, 63.5 min, 64 min, 64.5 min or 65 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional embodiments, the mass fraction of the glutaraldehyde solution is 2-2.5wt.%, for example, it can be 2.00wt.%, 2.05wt.%, 2.10wt.%, 2.15wt.%, 2.20wt.%, 2.25wt.%, 2.30wt.%, 2.35wt.%, 2.40wt.%, 2.45wt.% or 2.50wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional embodiments, the solid-to-liquid ratio of the polyaniline / cotton composite fiber to the glutaraldehyde solution is 1:(25-30), for example, it can be 1:25.0, 1:25.5, 1:26.0, 1:26.5, 1:27.0, 1:27.5, 1:28.0, 1:28.5, 1:29.0, 1:29.5 or 1:30.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In some optional embodiments, the activation time is 15-20 min, for example, it can be 15.0 min, 15.5 min, 16.0 min, 16.5 min, 17.0 min, 17.5 min, 18.0 min, 18.5 min, 19.0 min, 19.5 min or 20.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In some optional embodiments, the stirring speed during activation is 200-250rpm, for example, it can be 200rpm, 205rpm, 210rpm, 215rpm, 220rpm, 225rpm, 230rpm, 235rpm, 240rpm, 245rpm or 250rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some optional embodiments, the solid-liquid ratio of the polyaniline / cotton composite fiber to the modified dispersion after activation is 1:(20-25), for example, it can be 1:20, 1:20.5, 1:21.0, 1:21.5, 1:22.0, 1:22.5, 1:23.0, 1:23.5, 1:24.0, 1:24.5 or 1:25, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional embodiments, the stirring time at room temperature is 1-2h, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] As a preferred technical solution of the present invention, in S24, the concentration of the dodecylbenzenesulfonic acid solution is 0.2-0.3M, for example, it can be 0.20M, 0.21M, 0.22M, 0.23M, 0.24M, 0.25M, 0.26M, 0.27M, 0.28M, 0.29M or 0.30M, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some optional embodiments, the solid-to-liquid ratio of the modified polyaniline / cotton composite fiber to the dodecylbenzene sulfonic acid solution is 1:(35-40), for example, it can be 1:35.0, 1:35.5, 1:36.0, 1:36.5, 1:37.0, 1:37.5, 1:38.0, 1:38.5, 1:39.0, 1:39.5 or 1:40.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some optional embodiments, the modified polyaniline / cotton composite fiber is immersed in the dodecylbenzene sulfonic acid solution for 1.5-2h, for example, 1.50h, 1.55h, 1.60h, 1.65h, 1.70h, 1.75h, 1.80h, 1.85h, 1.90h, 1.95h or 2.00h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some optional embodiments, the mass fraction of the quaternary ammonium salt antistatic agent solution is 0.8-1.2wt.%, for example, it can be 0.80wt.%, 0.84wt.%, 0.88wt.%, 0.92wt.%, 0.96wt.%, 1.00wt.%, 1.04wt.%, 1.08wt.%, 1.12wt.% or 1.20wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In some optional embodiments, the pH is adjusted to 5.3-5.7 with acetic acid, for example, 5.30, 5.34, 5.38, 5.42, 5.46, 5.50, 5.54, 5.58, 5.62, 5.66 or 5.70, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional embodiments, the solid-liquid ratio of the doped modified fiber to the antistatic impregnation liquid is 1:(30-35), for example, it can be 1:30.0, 1:30.5, 1:31.0, 1:31.5, 1:32.0, 1:32.5, 1:33.0, 1:33.5, 1:34.0, 1:34.5 or 1:35.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional embodiments, the constant temperature stirring temperature is 30-35°C, for example, it can be 30.0°C, 30.5°C, 31.0°C, 31.5°C, 32.0°C, 32.5°C, 33.0°C, 33.5°C, 34.0°C, 34.5°C or 35.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In some optional embodiments, the constant temperature stirring speed is 150-200rpm, for example, it can be 150rpm, 155rpm, 160rpm, 165rpm, 170rpm, 175rpm, 180rpm, 185rpm, 190rpm, 195rpm or 200rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In some optional embodiments, the constant temperature stirring time is 20-30 min, for example, it can be 20.0 min, 21.0 min, 22.0 min, 23.0 min, 24.0 min, 25.0 min, 26.0 min, 27.0 min, 28.0 min, 29.0 min or 30.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In the present invention, polyester fiber is selected as the substrate. Polyester fiber is a polymer material with excellent performance and wide application. It is mainly formed by polycondensation of terephthalic acid and ethylene glycol. In its molecular structure, ester groups connect benzene rings and ethylene glycol units to form a linear polymer chain. The ester group is a group with a certain polarity. The polar force between molecules makes the polyester fiber have good chemical stability and heat resistance. The presence of the ester group not only enhances the interaction between molecular chains, but also enables the polyester fiber to maintain stable physical and chemical properties in a wide temperature range.
[0062] The molecular chain structure of polyester fiber also contains benzene rings and ethylene glycol units. The synergistic effect of these structural units makes the fiber show good comprehensive mechanical properties. The benzene ring provides rigidity and heat resistance, giving polyester fiber high tensile strength and wear resistance; the ethylene glycol unit brings a certain flexibility to the molecular chain, so that the fiber shows good toughness and ductility when subjected to stress. Due to the structural characteristics of these molecular chains, polyester fiber has a high degree of mechanical stability, is not easy to be broken, and can maintain dimensional stability under high load conditions for a long time. This high strength and toughness make it an ideal skeleton for various reinforcing materials.
[0063] In addition, the molecular structure of polyester fiber determines the unique properties of its surface. The hydrophobicity of the polyester fiber surface comes from the presence of non-polar alkyl and benzene rings in the molecule, which makes it less likely to absorb water and also increases its anti-pollution performance. Due to its hydrophobicity and chemical inertness, polyester fiber is not easily degraded in humid or complex environments and can resist corrosion from a variety of chemical agents (such as acids and alkalis). This chemical corrosion resistance not only extends the service life of polyester fiber, but also makes it widely used in industrial fields that require weather resistance and corrosion resistance.
[0064] In the present invention, polyester fiber is used as a substrate, and its main contribution is its excellent strength, flexibility and environmental resistance. These characteristics enable polyester fiber to maintain good mechanical properties and chemical stability under a variety of complex conditions, becoming an indispensable component of composite materials. However, it should be noted that polyester fiber itself is an electrical insulator. Since its molecular chain lacks free electrons or ion conduction channels, the electrical conductivity of the body is extremely low, so it cannot be directly applied in the field of electrical conduction. In order to give it conductive properties, the surface of polyester fiber can be functionalized by a variety of chemical treatment methods.
[0065] In order to make the polyester fiber conductive and functional, the present invention chemically modifies it so that it can meet the application requirements in conductive textiles and other functional composite materials. Polyester fiber itself is a high-strength, chemically resistant material, but due to the lack of free electrons and ion conduction channels in the molecular chain, its body is an electrical insulator. Therefore, giving it conductivity and multifunctionality through surface modification is the key to achieving its high value-added application.
[0066] First, the polyester fiber is activated with sodium dodecylbenzene sulfonate. Sodium dodecylbenzene sulfonate is an anionic surfactant that contains hydrophobic long-chain alkyl groups and hydrophilic sulfonic acid groups in its molecular structure. During the treatment process, sodium dodecylbenzene sulfonate is adsorbed on the hydrophobic surface of the polyester fiber through hydrophobic action, while its sulfonic acid groups are exposed to the outside, giving the fiber surface a negative charge and forming a negatively charged activation layer. This activation layer not only improves the hydrophilicity of the fiber surface, but also provides charge binding sites for the subsequent adsorption of metal ions (such as silver ions) and other chemicals, thereby enhancing the efficiency of the chemical modification process.
[0067] Secondly, the surface of the polyester fiber is modified using a phosphoric acid solution. Phosphoric acid is a weakly acidic chemical reagent. During the treatment process, it can partially hydrolyze the ester bonds on the surface of the polyester fiber to generate a small amount of hydroxyl groups. These hydroxyl groups further react with phosphoric acid molecules to generate phosphate groups. Phosphate groups have the following multiple functions: phosphate groups can bind to silver ions or other metal ions through coordination bonds to form stable chemical complexes, providing the necessary attachment points for subsequent metal deposition; secondly, the introduction of phosphate groups significantly increases the polarity of the fiber surface (due to the high electron density of phosphate groups), thereby increasing the surface energy of the fiber surface. This increase in surface energy makes it easier for polyester fibers to adsorb various functional materials, including metal nanoparticles, conductive polymers, and water-soluble chemical reagents; at the same time, phosphoric acid treatment also makes the fiber surface rough through slight chemical corrosion. This surface roughening further increases the specific surface area and adhesion ability of the fiber, providing physical and chemical dual enhancement for subsequent chemical coating.
[0068] The mass fraction of the phosphoric acid solution is limited to 10-15wt.% in the present invention. When the mass fraction of the phosphoric acid solution is too low, the active sites on the surface of the activated polyester fiber obtained will be insufficient, and the binding force between the activated polyester fiber and the subsequent silver layer will be poor, thereby making the conductivity of the final textile fabric insufficient. When the mass fraction of the phosphoric acid solution is too high, the surface of the activated polyester fiber will be excessively corroded, and its mechanical properties will be reduced.
[0069] The activated polyester fiber is immersed in a silver ammonia solution for silver plating. + It is a stable silver ion complex in which the silver ion is stabilized by the coordination of the ammonia molecule. Since the fiber surface carries the negative charge of sodium dodecylbenzene sulfonate, [Ag(NH3)2] + The silver ions in the polyester fiber can be adsorbed on the fiber surface through electrostatic action. In addition, the phosphate groups on the fiber surface can further enhance the adsorption efficiency of silver ions through coordination. Subsequently, under the action of ascorbic acid, the silver ions are reduced to metallic silver, and the reduced metallic silver is gradually deposited on the fiber surface to form a uniform and dense conductive silver film. This silver film not only gives the polyester fiber excellent conductive properties, but also maintains the flexibility and mechanical strength of the fiber, making it suitable for use as a flexible conductive material.
[0070] Next, in order to further give the fiber multifunctionality, β-cyclodextrin was used to modify the surface of the silver-plated fiber. β-cyclodextrin is a cyclic oligosaccharide composed of 7 glucose units connected by α-1,4 glycosidic bonds. Its molecular structure has unique internal and external amphiphilic properties: the inner cavity is hydrophobic and can accommodate hydrophobic small molecule guests through hydrophobic interaction or van der Waals force; the outer ring is composed of hydroxyl groups on the glucose units and is highly hydrophilic. When β-cyclodextrin is modified on the surface of the silver-plated fiber, the hydroxyl groups on its outer ring are exposed to the outside, which significantly enhances the hydrophilicity of the fiber surface. This modification has the following advantages: the hydrophobic inner cavity of β-cyclodextrin can capture a variety of hydrophobic molecules, such as antibacterial agents (such as tea polyphenols), dye molecules or catalyst molecules, thereby giving the fiber antibacterial properties, dyeing properties or catalytic activity; secondly, after silver plating, the silver layer on the fiber surface usually exhibits low hydrophilicity, while the hydrophobicity of the polyester fiber itself comes from the hydrophobic parts of the benzene ring and ester group in its molecular structure. By modifying β-cyclodextrin, the hydrophilicity of the fiber surface is significantly improved, making it easier to interact with water-soluble functional agents in an aqueous environment, improving the wettability of the fiber, and optimizing the comfort of the final textile; in addition, β-cyclodextrin forms a stable molecular coating on the fiber surface, which can effectively slow down the oxidation process of the silver layer. Specifically, when the silver layer is exposed to the air, it easily reacts with sulfide to form silver sulfide, resulting in a decrease in conductivity. The protective layer of β-cyclodextrin can reduce the direct contact between the silver layer and sulfide in the air, thereby delaying its oxidation and corrosion.
[0071] In the present invention, cotton fiber is selected as the substrate. Cotton fiber is a natural polymer material with a wide range of sources and is renewable. It is widely used in the field of textiles and functional composite materials. The main component of cotton fiber is cellulose. Cellulose is a linear natural polymer composed of glucose units connected by β-1,4-glycosidic bonds, and its molecular formula is (C6H 10 O5) n Cellulose molecules contain a large number of hydroxyl groups, which are highly chemically reactive, allowing cellulose to undergo a variety of reactions with other chemical reagents. For example, by chemically grafting conductive polymers (such as polyaniline) or combining with nanomaterials (such as graphene) through physical adsorption, composite materials with conductivity or other functions can be developed.
[0072] The microstructure of cotton fiber is highly porous and has a large surface area, which can provide abundant physical adsorption sites for the bonding of conductive materials. In addition, the polarity of the cellulose molecular chain enables its surface to adsorb functional materials (such as carbon nanotubes or graphene) through hydrogen bonding, electrostatic interaction or van der Waals force, thereby realizing the functionalization of the material. Cotton fiber also has good softness and hygroscopicity, which comes from the fact that the hydroxyl groups in its cellulose molecules can hydrogen bond with water molecules. These characteristics of cotton fiber not only make it widely used in the field of traditional textiles, but also lay the foundation for it to be an ideal substrate for functional composite materials.
[0073] In order to give the cotton fiber conductive properties, the present application performs pretreatment and polyaniline coating on it. First, the cotton fiber is pretreated by dipping in a hydrochloric acid solution. Hydrochloric acid can protonate the hydroxyl groups in the cellulose molecular chain, thereby introducing positive charges on the fiber surface. This process not only increases the electrostatic attraction between the fiber surface and the aniline monomer, but also improves the fiber's adsorption capacity for the aniline monomer. In addition, the acidic environment of hydrochloric acid can also improve the efficiency of subsequent polymerization reactions, providing a good chemical environment for the uniform deposition of polyaniline.
[0074] On the surface of cotton fibers treated with hydrochloric acid, aniline monomers are converted into polyaniline through chemical oxidative polymerization. Specifically, aniline monomers undergo oxidation reactions in a hydrochloric acid environment with ammonium persulfate as an oxidant to generate aniline cationic free radicals. These free radicals undergo chain growth reactions on the fiber surface to form polyaniline molecular chains with a conjugated structure. Through this reaction, polyaniline is uniformly deposited on the surface of cotton fibers to form a continuous polyaniline coating. This coating is firmly attached to the fiber surface and can effectively give the fiber conductive properties while maintaining the fiber's flexibility and mechanical strength.
[0075] In the present invention, graphene and carbon nanotubes are introduced to modify cotton fibers. Both graphene and carbon nanotubes are excellent conductive materials, wherein carbon nanotubes have excellent electronic conductivity due to their one-dimensional conjugated structure, while graphene has ultra-high carrier mobility and a large specific surface area, which can provide a wider range of electron transmission channels. In addition, carbon nanotubes not only have extremely high electrical conductivity, but can also be combined with the fiber surface through van der Waals force or π-π action. The synergistic effect of the two nanomaterials provides an important basis for the composite fiber to form a multi-dimensional conductive network and achieve mechanical enhancement.
[0076] In order to realize the uniform dispersion of nano material in water phase, polyvinyl pyrrolidone and sodium dodecyl benzene sulfonate are used as dispersants in the present invention. The hydrophobic segment in the polyvinyl pyrrolidone molecule can be combined with graphene or carbon nanotube surface by non-covalent action, and its hydrophilic segment interacts with water molecules by hydrogen bond, thereby significantly improving the dispersion stability of nano material in water phase. In this system, the graphene surface lacks oxidized groups, and the synergistic effect of polyvinyl pyrrolidone and sodium dodecyl benzene sulfonate is more important, to help graphene form stable suspension dispersion in water phase. This uniformly dispersed nano material can better adhere to the fiber surface, forming a more complete coating.
[0077] In order to further enhance the fixation of graphene and carbon nanotubes on the fiber surface, the present invention uses glutaraldehyde as a crosslinking agent. The aldehyde group in glutaraldehyde can react with the hydroxyl group in the cellulose molecule to form a stable covalent crosslinking network. Through this crosslinking, more binding sites can be provided on the fiber surface, indirectly improving the adhesion strength of graphene and carbon nanotubes, thereby significantly enhancing the structural stability and electrical conductivity of the composite material.
[0078] In addition, the present application also modifies polyaniline by using dodecylbenzene sulfonic acid as a dopant. Dodecylbenzene sulfonic acid is a strong acidic dopant that protonates the amine groups in the polyaniline molecular chain, stabilizes its conjugated structure, and significantly improves the conductive properties of polyaniline. At the same time, a quaternary ammonium salt antistatic agent is introduced into the system to effectively shield the accumulation of static charges by forming an ion layer on the fiber surface, thereby further optimizing the antistatic properties of the composite material.
[0079] The concentration of the dopant dodecylbenzenesulfonic acid solution is limited to 0.2-0.3M in the present invention. When the concentration of the dopant solution is too high, excessive dodecylbenzenesulfonic acid molecules are enriched on the surface of the cotton fiber, thereby increasing the molecular chain spacing, forming a rigid structure, and reducing the flexibility of the textile fabric; when the concentration of the dopant solution is too low, the doping degree is insufficient, the protonation degree of the polyaniline molecular chain is low, the conductive state conversion is incomplete, the electronic transmission of the fiber is blocked, and the conductive performance is reduced.
[0080] There is also a synergistic reinforcement effect in the system of the present invention. In terms of mechanical properties: polyester fiber provides high strength and wear resistance, and can be used as a skeleton material for textile fabrics; while cotton fiber provides flexibility and comfort, making the fabric more close-fitting. In addition, the two-dimensional layer structure of graphene can disperse stress between fibers, and the one-dimensional nano-enhancement effect of carbon nanotubes significantly improves the tensile strength and durability of the composite fiber. The synergistic effect of the three forms a strong and soft composite structure, which makes the composite material show excellent performance in mechanical properties.
[0081] In terms of conductivity: the silver layer on the surface of polyester fiber provides excellent conductivity, and the polyaniline and nanomaterials on the surface of cotton fiber form a stable conductive network. The two-dimensional conductive sheet of graphene and the one-dimensional conductive path of carbon nanotubes work together as an "electronic bridge" to connect the conductive nodes between different fibers, forming an efficient conductive path, thereby significantly improving the overall conductivity of the composite material.
[0082] The synergistic effect on the interface bonding is as follows: β-cyclodextrin enhances the bonding ability between the polyester fiber surface and the conductive component (such as silver layer or polyaniline) through its host-guest effect; at the same time, glutaraldehyde forms a cross-linked structure by reacting with the hydroxyl group of cellulose to form an acetalization reaction, thereby significantly improving the bonding strength between the cotton fiber and the nanomaterial. In addition, the two fibers further enhance the stability of the composite structure and improve the overall performance through physical entanglement and chemical interface interaction during the textile process.
[0083] In a second aspect, the present invention provides a textile fabric.
[0084] Compared with the prior art, the present invention has the following beneficial effects: The present invention selects polyester fiber and cotton fiber as the base material. The synergistic effect of the ester group and the benzene ring in the molecular structure gives the fiber high strength, wear resistance and chemical stability. At the same time, the hydrophobicity of the surface improves its anti-pollution and corrosion resistance. Cotton fiber is composed of cellulose, and the abundant hydroxyl groups in the molecular chain give it good chemical reaction activity and flexibility, making it an ideal base material for functional modification.
[0085] In the present invention, the polyester fiber is first treated with sodium dodecylbenzene sulfonate to form a negatively charged activation layer on its surface, and then treated with phosphoric acid to generate phosphate groups, which enhances the polarity and adsorption capacity of the fiber surface and provides attachment sites for the subsequent deposition of silver ions. In the silver ammonia solution, the silver ions are adsorbed on the fiber surface through electrostatic action and coordination bonds, and are reduced to metallic silver under the action of ascorbic acid to form a uniform conductive silver film. In order to further improve the functionality, β-cyclodextrin is used to modify the surface of the silver film, enhance the hydrophilicity and antioxidant properties of the fiber, and give it the function of capturing small molecules.
[0086] The cotton fiber in the present invention is pretreated with hydrochloric acid to enhance the binding ability with aniline monomer. Aniline is chemically oxidized and polymerized under the action of hydrochloric acid and ammonium persulfate to form a conductive polyaniline coating uniformly deposited on the surface of the cotton fiber. In addition, graphene and carbon nanotubes are introduced as conductive reinforcing materials. The high specific surface area of graphene and the one-dimensional conjugated structure of carbon nanotubes can synergistically construct a multidimensional conductive network to improve the conductivity of the composite fiber. The graphene and carbon nanotubes are uniformly dispersed by polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate dispersants, and the binding strength on the fiber surface is enhanced by cross-linking with glutaraldehyde. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] Figure 1 This is a scanning electron microscope image of the silver-plated modified polyester fiber provided in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the polyaniline / cotton composite fiber provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0088] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0089] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products without further purification or treatment.
[0090] Polyester fiber: with a fineness of 1 dtex and a length of 30 mm, purchased from Zibo Baina New Material Technology Co., Ltd.
[0091] Example 1
[0092] This embodiment provides a textile fabric and a preparation method thereof, and the preparation method of the textile fabric specifically comprises the following steps: 76 parts by mass of modified polyester fiber and 22 parts by mass of conductive composite fiber are uniformly mixed and spun to form a textile fabric; The preparation method of the modified polyester fiber is: S11: ultrasonically cleaning the polyester fiber with anhydrous ethanol to obtain a pretreated polyester fiber; adding sodium dodecylbenzene sulfonate to a phosphoric acid solution to obtain an activation solution, and immersing the pretreated polyester fiber in the activation solution to obtain an activated polyester fiber; Specifically, S11: ultrasonically clean the polyester fiber with anhydrous ethanol and then dry it to obtain a pretreated polyester fiber; add sodium dodecylbenzene sulfonate to a phosphoric acid solution with a mass fraction of 15wt.% to obtain an activation solution, wherein the amount of sodium dodecylbenzene sulfonate in the activation solution is 1.0g / L, immerse the pretreated polyester fiber in the activation solution, wherein the solid-liquid ratio of the pretreated polyester fiber to the activation solution is 1:20, stir and react at a constant temperature of 60°C for 15min, wherein the stirring speed is 200rpm, take out, wash, and dry to obtain the activated polyester fiber; S12: mixing silver nitrate, ethylenediaminetetraacetic acid and ammonia water to obtain a silver ammonia solution, immersing the activated polyester fiber in the silver ammonia solution, stirring and immersing, and then dropping an ascorbic acid solution to react to obtain a silver-plated modified polyester fiber; Specifically, S12: silver nitrate, ethylenediaminetetraacetic acid and ammonia water are mixed to obtain a silver ammonia solution, wherein the concentration of silver nitrate in the silver ammonia solution is 0.2M, the concentration of ethylenediaminetetraacetic acid in the silver ammonia solution is 2-3g / L, ammonia water is added to make the pH of the silver ammonia solution reach 9, and the activated polyester fiber is immersed in the silver ammonia solution at a solid-liquid ratio of 1:30, and after stirring and immersing at room temperature, an ascorbic acid solution with a concentration of 20g / L is added at a dropping speed of 2.3mL / min, wherein the molar ratio of ascorbic acid to silver nitrate is 0.8:1, and the reaction is stirred at 20°C at a speed of 150rpm for 28min, and then washed and dried to obtain a silver-plated modified polyester fiber; its scanning electron microscopy is as follows Figure 1 As shown, a layer of conductive silver film deposited on the surface of the polyester fiber can be observed, which can effectively give the polyester fiber conductive properties.
[0093] S13: preparing a β-cyclodextrin solution, adjusting the pH thereof with a sodium hydroxide solution to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution, and reacting to obtain the modified polyester fiber.
[0094] Specifically, S13: preparing a β-cyclodextrin solution with a mass fraction of 1.5 wt.%, adjusting the pH of the β-cyclodextrin solution to 6 with a sodium hydroxide solution with a concentration of 0.2 M to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution with a solid-liquid ratio of 1:20, stirring at a constant temperature of 52° C. and a speed of 160 rpm for 92 min, and then washing and drying to obtain the modified polyester fiber; The preparation method of the conductive composite fiber comprises: S21: ultrasonically cleaning the cotton fiber with anhydrous ethanol and then drying it to obtain a first pretreated cotton fiber; immersing the first pretreated cotton fiber in a 0.8M hydrochloric acid solution at a solid-liquid ratio of 1:33, and immersing it at room temperature for 12.5 minutes to obtain a pretreated cotton fiber; S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing the solution in an ice water bath for later use, adding aniline monomer to the hydrochloric acid solution to obtain a monomer solution, immersing the pretreated cotton fiber in the monomer solution, stirring and then dropping the oxidant solution to obtain a polyaniline / cotton composite fiber; Specifically, S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing it in an ice-water bath for standby use, wherein the concentration of ammonium persulfate in the oxidant solution is 0.25 M; adding aniline monomer to a hydrochloric acid solution to obtain a monomer solution, wherein the concentration of aniline monomer in the monomer solution is 0.23 M, immersing the pretreated cotton fiber in the monomer solution at a solid-liquid ratio of 1:30 under ice-water bath conditions, and adding dropwise the oxidant solution after stirring, wherein the molar ratio of aniline monomer to ammonium persulfate is 1:1, continuing to stir the reaction for 3.4 hours, washing, and drying to obtain a polyaniline / cotton composite fiber; Figure 2 This is a scanning electron microscope image of polyaniline / cotton composite fiber. Polyaniline is evenly deposited on the surface of the cotton fiber to form a continuous polyaniline coating, which effectively gives the cotton fiber conductive properties.
[0095] S23: adding polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to deionized water to obtain a dispersion base solution, and adding graphene and carbon nanotubes to obtain a modified dispersion solution; immersing the polyaniline / cotton composite fiber in a glutaraldehyde solution for activation, taking it out, washing it, and immersing it in the modified dispersion solution to react and obtain a modified polyaniline / cotton composite fiber; Specifically, S23: adding polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to deionized water to obtain a dispersion base liquid, adding graphene and carbon nanotubes, and ultrasonically dispersing under ice-water bath conditions to obtain a modified dispersion liquid, wherein the mass ratio of graphene to carbon nanotubes is 1:1, the concentration of the mixture of graphene and carbon nanotubes is 1.42 mg / mL, the mass fraction of polyvinyl pyrrolidone in the modified dispersion liquid is 0.98wt.%, the mass fraction of sodium dodecylbenzene sulfonate in the modified dispersion liquid is 0.2wt.%, and the power of ultrasonic dispersion is 160W and the time is 62min; immersing the polyaniline / cotton composite fiber in a glutaraldehyde solution with a mass fraction of 2.5wt.%, wherein the solid-liquid ratio of the polyaniline / cotton composite fiber to the glutaraldehyde solution is 1:25, activating at a speed of 230rpm for 16min, taking out, washing, and immersing in the modified dispersion liquid with a solid-liquid ratio of 1:20, stirring at room temperature for 1h, taking out, washing, and drying to obtain the modified polyaniline / cotton composite fiber; S24: immersing the modified polyaniline / cotton composite fiber in a dodecylbenzene sulfonic acid solution to obtain a doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution, adjusting the pH with acetic acid to obtain an antistatic impregnation solution, and immersing the doped modified fiber in the solution to obtain a conductive composite fiber.
[0096] Specifically, S24: immersing the modified polyaniline / cotton composite fiber in a 0.25M dodecylbenzene sulfonic acid solution, wherein the solid-liquid ratio of the modified polyaniline / cotton composite fiber to the dodecylbenzene sulfonic acid solution is 1:35, the immersion temperature is 42°C, and the immersion time is 1.5h, washing and drying to obtain the doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution with a mass fraction of 1.2wt.%, adjusting the pH to 5.3 with acetic acid to obtain an antistatic impregnation solution, immersing the doped modified fiber at a solid-liquid ratio of 1:30, stirring at a constant temperature of 33°C and a speed of 170rpm for 22min, taking out, washing, and drying to obtain a conductive composite fiber.
[0097] Example 2 This embodiment provides a textile fabric and a preparation method thereof, and the preparation method of the textile fabric specifically comprises the following steps: 80 parts by weight of modified polyester fiber and 26 parts by weight of conductive composite fiber are uniformly mixed and woven to form a textile fabric; The preparation method of the modified polyester fiber is: S11: ultrasonically cleaning the polyester fiber with anhydrous ethanol to obtain a pretreated polyester fiber; adding sodium dodecylbenzene sulfonate to a phosphoric acid solution to obtain an activation solution, and immersing the pretreated polyester fiber in the activation solution to obtain an activated polyester fiber; Specifically, S11: ultrasonically clean the polyester fiber with anhydrous ethanol and then dry it to obtain a pretreated polyester fiber; add sodium dodecylbenzene sulfonate to a phosphoric acid solution with a mass fraction of 10wt.% to obtain an activation solution, wherein the amount of sodium dodecylbenzene sulfonate in the activation solution is 0.5g / L, immerse the pretreated polyester fiber in the activation solution, wherein the solid-liquid ratio of the pretreated polyester fiber to the activation solution is 1:30, stir and react at a constant temperature of 65°C for 20min, wherein the stirring speed is 250rpm, take out, wash, and dry to obtain the activated polyester fiber; S12: mixing silver nitrate, ethylenediaminetetraacetic acid and ammonia water to obtain a silver ammonia solution, immersing the activated polyester fiber in the silver ammonia solution, stirring and immersing, and then dropping an ascorbic acid solution to react to obtain a silver-plated modified polyester fiber; Specifically, S12: silver nitrate, ethylenediaminetetraacetic acid and ammonia water are mixed to obtain a silver ammonia solution, wherein the concentration of silver nitrate in the silver ammonia solution is 0.12M, the concentration of ethylenediaminetetraacetic acid in the silver ammonia solution is 2g / L, ammonia water is added to make the pH of the silver ammonia solution reach 9.5, and the activated polyester fiber is immersed in the silver ammonia solution at a solid-liquid ratio of 1:33, and after stirring and immersing at room temperature, an ascorbic acid solution with a concentration of 18g / L is added at a dropping speed of 2.7mL / min, wherein the molar ratio of ascorbic acid to silver nitrate is 0.9:1, and the reaction is stirred at 25°C at a rotation speed of 170rpm for 30min, and then washed and dried to obtain a silver-plated modified polyester fiber; S13: preparing a β-cyclodextrin solution, adjusting the pH thereof with a sodium hydroxide solution to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution, and reacting to obtain the modified polyester fiber.
[0098] Specifically, S13: preparing a β-cyclodextrin solution with a mass fraction of 1.2 wt.%, adjusting the pH of the β-cyclodextrin solution to 7 with a sodium hydroxide solution with a concentration of 0.12 M to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution with a solid-liquid ratio of 1:27, stirring at a constant temperature of 53° C. and a speed of 200 rpm for 96 min, and then washing and drying to obtain the modified polyester fiber; The preparation method of the conductive composite fiber comprises: S21: ultrasonically cleaning the cotton fiber with anhydrous ethanol and then drying it to obtain a first pretreated cotton fiber; immersing the first pretreated cotton fiber in a 1M hydrochloric acid solution with a solid-liquid ratio of 1:30, and immersing it at room temperature for 14.5 minutes to obtain a pretreated cotton fiber; S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing the solution in an ice water bath for later use, adding aniline monomer to the hydrochloric acid solution to obtain a monomer solution, immersing the pretreated cotton fiber in the monomer solution, stirring and then dropping the oxidant solution to obtain a polyaniline / cotton composite fiber; Specifically, S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing it in an ice-water bath for later use, wherein the concentration of ammonium persulfate in the oxidant solution is 0.3 M; adding aniline monomer to a hydrochloric acid solution to obtain a monomer solution, wherein the concentration of aniline monomer in the monomer solution is 0.25 M, immersing the pretreated cotton fiber in the monomer solution at a solid-liquid ratio of 1:35 under ice-water bath conditions, and adding dropwise the oxidant solution after stirring, wherein the molar ratio of aniline monomer to ammonium persulfate is 1:1.25, continuing to stir the reaction for 3.7 hours, washing, and drying to obtain a polyaniline / cotton composite fiber; S23: adding polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to deionized water to obtain a dispersion base solution, and adding graphene and carbon nanotubes to obtain a modified dispersion solution; immersing the polyaniline / cotton composite fiber in a glutaraldehyde solution for activation, taking it out, washing it, and immersing it in the modified dispersion solution to react and obtain a modified polyaniline / cotton composite fiber; Specifically, S23: adding polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to deionized water to obtain a dispersion base liquid, adding graphene and carbon nanotubes, and ultrasonically dispersing under ice-water bath conditions to obtain a modified dispersion liquid, wherein the mass ratio of graphene to carbon nanotubes is 2:1, the concentration of the mixture of graphene and carbon nanotubes is 1.35 mg / mL, the mass fraction of polyvinyl pyrrolidone in the modified dispersion liquid is 1.1wt.%, and the mass fraction of sodium dodecylbenzene sulfonate in the modified dispersion liquid is 0.3wt.%, and the power of ultrasonic dispersion is 180W and the time is 44min; immersing the polyaniline / cotton composite fiber in a glutaraldehyde solution with a mass fraction of 2wt.%, wherein the solid-liquid ratio of the polyaniline / cotton composite fiber to the glutaraldehyde solution is 1:27, activating at a speed of 250rpm for 20min, taking out, and after washing, immersing in the modified dispersion liquid with a solid-liquid ratio of 1:25, stirring at room temperature for 1.2h, taking out, washing, and drying to obtain the modified polyaniline / cotton composite fiber; S24: immersing the modified polyaniline / cotton composite fiber in a dodecylbenzene sulfonic acid solution to obtain a doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution, adjusting the pH with acetic acid to obtain an antistatic impregnation solution, and immersing the doped modified fiber in the solution to obtain a conductive composite fiber.
[0099] Specifically, S24: immersing the modified polyaniline / cotton composite fiber in a dodecylbenzene sulfonic acid solution with a concentration of 0.23M, wherein the solid-liquid ratio of the modified polyaniline / cotton composite fiber to the dodecylbenzene sulfonic acid solution is 1:40, the immersion temperature is 45°C, and the immersion time is 2h, washing and drying to obtain the doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution with a mass fraction of 0.8wt.%, adjusting the pH to 5.4 with acetic acid to obtain an antistatic impregnation solution, immersing the doped modified fiber at a solid-liquid ratio of 1:32, stirring at a constant temperature of 37°C and a speed of 180rpm for 28min, taking out, washing, and drying to obtain a conductive composite fiber.
[0100] Example 3
[0101] This embodiment provides a textile fabric and a preparation method thereof, and the preparation method of the textile fabric specifically comprises the following steps: 70 parts by weight of modified polyester fiber and 20 parts by weight of conductive composite fiber are uniformly mixed and then woven into a textile fabric; The preparation method of the modified polyester fiber is: S11: ultrasonically cleaning the polyester fiber with anhydrous ethanol to obtain a pretreated polyester fiber; adding sodium dodecylbenzene sulfonate to a phosphoric acid solution to obtain an activation solution, and immersing the pretreated polyester fiber in the activation solution to obtain an activated polyester fiber; Specifically, S11: ultrasonically clean the polyester fiber with anhydrous ethanol and then dry it to obtain a pretreated polyester fiber; add sodium dodecylbenzene sulfonate to a phosphoric acid solution with a mass fraction of 13wt.% to obtain an activation solution, wherein the amount of sodium dodecylbenzene sulfonate in the activation solution is 0.8g / L, immerse the pretreated polyester fiber in the activation solution, wherein the solid-liquid ratio of the pretreated polyester fiber to the activation solution is 1:24, stir and react at a constant temperature of 62°C for 17min, wherein the stirring speed is 220rpm, take out, wash, and dry to obtain the activated polyester fiber; S12: mixing silver nitrate, ethylenediaminetetraacetic acid and ammonia water to obtain a silver ammonia solution, immersing the activated polyester fiber in the silver ammonia solution, stirring and immersing, and then dropping an ascorbic acid solution to react to obtain a silver-plated modified polyester fiber; Specifically, S12: silver nitrate, ethylenediaminetetraacetic acid and ammonia water are mixed to obtain a silver ammonia solution, wherein the concentration of silver nitrate in the silver ammonia solution is 0.1M, the concentration of ethylenediaminetetraacetic acid in the silver ammonia solution is 3g / L, ammonia water is added to make the pH of the silver ammonia solution reach 9.7, and the activated polyester fiber is immersed in the silver ammonia solution at a solid-liquid ratio of 1:36, and after stirring and immersing at room temperature, an ascorbic acid solution with a concentration of 16g / L is added at a dropping speed of 2mL / min, wherein the molar ratio of ascorbic acid to silver nitrate is 0.95:1, and the reaction is stirred at 21°C at a speed of 140rpm for 25min, and then washed and dried to obtain a silver-plated modified polyester fiber; S13: preparing a β-cyclodextrin solution, adjusting the pH thereof with a sodium hydroxide solution to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution, and reacting to obtain the modified polyester fiber.
[0102] Specifically, S13: preparing a β-cyclodextrin solution with a mass fraction of 1.3 wt.%, adjusting the pH of the β-cyclodextrin solution to 6.5 with a sodium hydroxide solution with a concentration of 0.15 M to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution with a solid-liquid ratio of 1:30, stirring at a constant temperature of 50° C. and a speed of 170 rpm for 90 min, and then washing and drying to obtain the modified polyester fiber; The preparation method of the conductive composite fiber comprises: S21: ultrasonically cleaning the cotton fiber with anhydrous ethanol and then drying it to obtain a first pretreated cotton fiber; immersing the first pretreated cotton fiber in a 0.5M hydrochloric acid solution at a solid-liquid ratio of 1:37, and immersing it at room temperature for 10 minutes to obtain a pretreated cotton fiber; S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing the solution in an ice water bath for later use, adding aniline monomer to the hydrochloric acid solution to obtain a monomer solution, immersing the pretreated cotton fiber in the monomer solution, stirring and then dropping the oxidant solution to obtain a polyaniline / cotton composite fiber; Specifically, S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing it in an ice-water bath for later use, wherein the concentration of ammonium persulfate in the oxidant solution is 0.27 M; adding aniline monomer to a hydrochloric acid solution to obtain a monomer solution, wherein the concentration of aniline monomer in the monomer solution is 0.2 M, immersing the pretreated cotton fiber in the monomer solution at a solid-liquid ratio of 1:32 under ice-water bath conditions, and adding dropwise the oxidant solution after stirring, wherein the molar ratio of aniline monomer to ammonium persulfate is 1:1.15, continuing to stir the reaction for 3 hours, washing, and drying to obtain a polyaniline / cotton composite fiber; S23: adding polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to deionized water to obtain a dispersion base solution, and adding graphene and carbon nanotubes to obtain a modified dispersion solution; immersing the polyaniline / cotton composite fiber in a glutaraldehyde solution for activation, taking it out, washing it, and immersing it in the modified dispersion solution to react and obtain a modified polyaniline / cotton composite fiber; Specifically, S23: adding polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to deionized water to obtain a dispersion base liquid, adding graphene and carbon nanotubes, and ultrasonically dispersing under ice-water bath conditions to obtain a modified dispersion liquid, wherein the mass ratio of graphene to carbon nanotubes is 1.5:1, the concentration of the mixture of graphene and carbon nanotubes is 1.2 mg / mL, the mass fraction of polyvinyl pyrrolidone in the modified dispersion liquid is 0.8 wt.%, and the mass fraction of sodium dodecylbenzene sulfonate in the modified dispersion liquid is 0.8 wt.%. The polyaniline / cotton composite fiber is 0.4wt.%, the power of ultrasonic dispersion is 150W, and the time is 40min; the polyaniline / cotton composite fiber is immersed in a glutaraldehyde solution with a mass fraction of 2.3wt.%, wherein the solid-liquid ratio of the polyaniline / cotton composite fiber to the glutaraldehyde solution is 1:28, and is activated at a speed of 210rpm for 18min and then taken out, and after washing, it is immersed in the modified dispersion liquid with a solid-liquid ratio of 1:22, and is stirred at room temperature for 1.8h and then taken out, washed, and dried to obtain the modified polyaniline / cotton composite fiber; S24: immersing the modified polyaniline / cotton composite fiber in a dodecylbenzene sulfonic acid solution to obtain a doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution, adjusting the pH with acetic acid to obtain an antistatic impregnation solution, and immersing the doped modified fiber in the solution to obtain a conductive composite fiber.
[0103] Specifically, S24: immersing the modified polyaniline / cotton composite fiber in a 0.2M dodecylbenzene sulfonic acid solution, wherein the solid-liquid ratio of the modified polyaniline / cotton composite fiber to the dodecylbenzene sulfonic acid solution is 1:36, the immersion temperature is 40°C, and the immersion time is 1.8h, washing and drying to obtain the doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution with a mass fraction of 1.12wt.%, adjusting the pH to 5.6 with acetic acid to obtain an antistatic impregnation solution, immersing the doped modified fiber at a solid-liquid ratio of 1:34, stirring at a constant temperature of 35°C and a speed of 150rpm for 20min, taking out, washing, and drying to obtain a conductive composite fiber.
[0104] Example 4
[0105] This embodiment provides a textile fabric and a preparation method thereof, and the preparation method of the textile fabric specifically comprises the following steps: 74 parts by weight of modified polyester fiber and 30 parts by weight of conductive composite fiber are uniformly mixed and spun to form a textile fabric; The preparation method of the modified polyester fiber is: S11: ultrasonically cleaning the polyester fiber with anhydrous ethanol to obtain a pretreated polyester fiber; adding sodium dodecylbenzene sulfonate to a phosphoric acid solution to obtain an activation solution, and immersing the pretreated polyester fiber in the activation solution to obtain an activated polyester fiber; Specifically, S11: ultrasonically clean the polyester fiber with anhydrous ethanol and then dry it to obtain a pretreated polyester fiber; add sodium dodecylbenzene sulfonate to a phosphoric acid solution with a mass fraction of 12wt.% to obtain an activation solution, wherein the amount of sodium dodecylbenzene sulfonate in the activation solution is 0.7g / L, immerse the pretreated polyester fiber in the activation solution, wherein the solid-liquid ratio of the pretreated polyester fiber to the activation solution is 1:28, stir and react at a constant temperature of 63°C for 18min, wherein the stirring speed is 230rpm, take out, wash, and dry to obtain the activated polyester fiber; S12: mixing silver nitrate, ethylenediaminetetraacetic acid and ammonia water to obtain a silver ammonia solution, immersing the activated polyester fiber in the silver ammonia solution, stirring and immersing, and then dropping an ascorbic acid solution to react to obtain a silver-plated modified polyester fiber; Specifically, S12: silver nitrate, ethylenediaminetetraacetic acid and ammonia water are mixed to obtain a silver ammonia solution, wherein the concentration of silver nitrate in the silver ammonia solution is 0.15M, the concentration of ethylenediaminetetraacetic acid in the silver ammonia solution is 2.7g / L, ammonia water is added to make the pH of the silver ammonia solution reach 10, and the activated polyester fiber is immersed in the silver ammonia solution at a solid-liquid ratio of 1:40, and after stirring and immersing at room temperature, an ascorbic acid solution with a concentration of 15g / L is added at a dropping speed of 3mL / min, wherein the molar ratio of ascorbic acid to silver nitrate is 1:1, and the reaction is stirred at 23°C at a speed of 200rpm for 30min, and then washed and dried to obtain a silver-plated modified polyester fiber; S13: preparing a β-cyclodextrin solution, adjusting the pH thereof with a sodium hydroxide solution to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution, and reacting to obtain the modified polyester fiber.
[0106] Specifically, S13: preparing a β-cyclodextrin solution with a mass fraction of 1 wt.%, adjusting the pH of the β-cyclodextrin solution to 6.9 with a sodium hydroxide solution with a concentration of 0.1 M to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution with a solid-liquid ratio of 1:22, stirring at a constant temperature of 55° C. and a speed of 180 rpm for 100 min, and then washing and drying to obtain the modified polyester fiber; The preparation method of the conductive composite fiber comprises: S21: ultrasonically cleaning the cotton fiber with anhydrous ethanol and then drying it to obtain a first pretreated cotton fiber; immersing the first pretreated cotton fiber in a 0.6M hydrochloric acid solution at a solid-liquid ratio of 1:40, and immersing it at room temperature for 15 minutes to obtain a pretreated cotton fiber; S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing the solution in an ice water bath for later use, adding aniline monomer to the hydrochloric acid solution to obtain a monomer solution, immersing the pretreated cotton fiber in the monomer solution, stirring and then dropping the oxidant solution to obtain a polyaniline / cotton composite fiber; Specifically, S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing it in an ice-water bath for standby use, wherein the concentration of ammonium persulfate in the oxidant solution is 0.28 M; adding aniline monomer to a hydrochloric acid solution to obtain a monomer solution, wherein the concentration of aniline monomer in the monomer solution is 0.24 M, immersing the pretreated cotton fiber in the monomer solution at a solid-liquid ratio of 1:33 under ice-water bath conditions, and adding dropwise the oxidant solution after stirring, wherein the molar ratio of aniline monomer to ammonium persulfate is 1:1.2, continuing to stir the reaction for 4 hours, washing, and drying to obtain a polyaniline / cotton composite fiber; S23: adding polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to deionized water to obtain a dispersion base solution, and adding graphene and carbon nanotubes to obtain a modified dispersion solution; immersing the polyaniline / cotton composite fiber in a glutaraldehyde solution for activation, taking it out, washing it, and immersing it in the modified dispersion solution to react and obtain a modified polyaniline / cotton composite fiber; Specifically, S23: adding polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to deionized water to obtain a dispersion base liquid, adding graphene and carbon nanotubes, and ultrasonically dispersing under ice-water bath conditions to obtain a modified dispersion liquid, wherein the mass ratio of graphene to carbon nanotubes is 1.2:1, the concentration of the mixture of graphene and carbon nanotubes is 1.5 mg / mL, the mass fraction of polyvinyl pyrrolidone in the modified dispersion liquid is 1.2wt.%, the mass fraction of sodium dodecylbenzene sulfonate in the modified dispersion liquid is 0.5wt.%, the power of ultrasonic dispersion is 200W, and the time is 45min; immersing the polyaniline / cotton composite fiber in a glutaraldehyde solution with a mass fraction of 2.2wt.%, wherein the solid-liquid ratio of the polyaniline / cotton composite fiber to the glutaraldehyde solution is 1:30, activating at a speed of 240rpm for 17min, taking out, washing, and immersing in the modified dispersion liquid with a solid-liquid ratio of 1:23, stirring at room temperature for 2h, taking out, washing, and drying to obtain the modified polyaniline / cotton composite fiber; S24: immersing the modified polyaniline / cotton composite fiber in a dodecylbenzene sulfonic acid solution to obtain a doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution, adjusting the pH with acetic acid to obtain an antistatic impregnation solution, and immersing the doped modified fiber in the solution to obtain a conductive composite fiber.
[0107] Specifically, S24: immersing the modified polyaniline / cotton composite fiber in a 0.3M dodecylbenzene sulfonic acid solution, wherein the solid-liquid ratio of the modified polyaniline / cotton composite fiber to the dodecylbenzene sulfonic acid solution is 1:38, the immersion temperature is 43°C, and the immersion time is 1.7h, washing and drying to obtain the doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution with a mass fraction of 1.07wt.%, adjusting the pH to 5.7 with acetic acid to obtain an antistatic impregnation solution, immersing the doped modified fiber at a solid-liquid ratio of 1:35, stirring at a constant temperature of 36°C and a speed of 200rpm for 30min, taking out, washing, and drying to obtain a conductive composite fiber.
[0108] Comparative Example 1 This comparative example provides a textile fabric, which is different from Example 1 in that, in S11, the mass fraction of the phosphoric acid solution is 30wt.%, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0109] Comparative Example 2 This comparative example provides a textile fabric, which is different from Example 1 in that, in S11, the mass fraction of the phosphoric acid solution is 5 wt.%, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0110] Comparative Example 3 This comparative example provides a textile fabric, which is different from Example 1 in that, in S24, the concentration of the dodecylbenzenesulfonic acid solution is 1 M, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0111] Comparative Example 4 This comparative example provides a textile fabric, which is different from Example 1 in that, in S24, the concentration of the dodecylbenzenesulfonic acid solution is 0.1 M, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0112] The performance test of the textile fabrics of the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 was carried out, and the specific process is as follows: Test the resistivity of the sample according to GB / T 12703.4-2010; According to GB / T 3923.1-2013, the breaking strength of the test sample is tested; The test results are shown in Table 1.
[0113] Table 1: Textile fabric performance test results of Example 1-Example 4 and Comparative Example 1-Comparative Example 4
[0114] It can be seen from the test results of Example 1 and Comparative Examples 1 and 2 that when the mass fraction of the phosphoric acid solution is too high, it will cause excessive corrosion on the surface of the activated polyester fiber and reduce its mechanical properties; when the mass fraction of the phosphoric acid solution is too low, it will lead to insufficient active sites on the surface of the activated polyester fiber, and its bonding force with the subsequent silver layer is poor, thereby making the conductivity of the final textile fabric insufficient.
[0115] From the test results of Example 1 and Comparative Examples 3 and 4, it can be seen that when the concentration of the dopant solution is too high, excessive dodecylbenzenesulfonic acid molecules are enriched on the surface of the cotton fiber, thereby increasing the molecular chain spacing, forming a rigid structure, and reducing the flexibility of the textile fabric; when the concentration of the dopant solution is too low, the doping degree is insufficient, the protonation degree of the polyaniline molecular chain is low, the conductive state conversion is incomplete, the electron transport of the fiber is hindered, and the conductive performance is reduced.
[0116] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a textile fabric, characterized in that: 70-80 parts by weight of modified polyester fiber and 20-30 parts by weight of conductive composite fiber are uniformly mixed and then woven into a textile fabric; The preparation method of the modified polyester fiber is: S11: ultrasonically cleaning the polyester fiber with anhydrous ethanol to obtain a pretreated polyester fiber; adding sodium dodecylbenzene sulfonate to a phosphoric acid solution to obtain an activation solution, and immersing the pretreated polyester fiber in the activation solution to obtain an activated polyester fiber; S12: mixing silver nitrate, ethylenediaminetetraacetic acid and ammonia water to obtain a silver ammonia solution, immersing the activated polyester fiber in the silver ammonia solution, stirring and immersing, and then dropping an ascorbic acid solution to react to obtain a silver-plated modified polyester fiber; S13: preparing a β-cyclodextrin solution, adjusting the pH thereof with a sodium hydroxide solution to obtain a functionalized solution, immersing the silver-plated modified polyester fiber in the functionalized solution, and reacting to obtain a modified polyester fiber; The mass fraction of the phosphoric acid solution is 10-15wt.%; The dosage of sodium dodecylbenzene sulfonate in the activation solution is 0.5-1.0 g / L; The concentration of silver nitrate in the silver ammonia solution is 0.1-0.2M; The concentration of EDTA in the silver ammonia solution is 2-3 g / L; Add ammonia water to make the pH of the silver ammonia solution reach 9-10; The concentration of the ascorbic acid solution is 15-20 g / L; The molar ratio of ascorbic acid to silver nitrate is (0.8-1):1; The mass fraction of the β-cyclodextrin solution is 1-1.5wt.%; The solid-to-liquid ratio of the silver-plated modified polyester fiber to the functionalized solution is 1:(20-30).
2. The method for preparing a textile fabric according to claim 1, characterized in that: In S11: The solid-to-liquid ratio of the pretreated polyester fiber to the activation solution is 1:(20-30).
3. The method for preparing a textile fabric according to claim 1, characterized in that: In S12: The solid-to-liquid ratio of the activated polyester fiber to the silver ammonia solution is 1:(30-40); The dropping speed of the ascorbic acid solution is 2-3 mL / min.
4. The method for preparing a textile fabric according to claim 1, characterized in that: In S13: The concentration of the sodium hydroxide solution is 0.1-0.2M; The sodium hydroxide solution adjusts the pH of the β-cyclodextrin solution to 6-7.
5. The method for preparing a textile fabric according to claim 1, characterized in that: The preparation method of the conductive composite fiber comprises: S21: ultrasonically cleaning the cotton fiber with anhydrous ethanol and then drying it to obtain a first pretreated cotton fiber; immersing the first pretreated cotton fiber in a hydrochloric acid solution at room temperature to obtain a pretreated cotton fiber; S22: adding ammonium persulfate to a hydrochloric acid solution to obtain an oxidant solution and placing the solution in an ice water bath for later use, adding aniline monomer to the hydrochloric acid solution to obtain a monomer solution, immersing the pretreated cotton fiber in the monomer solution, stirring and then dropping the oxidant solution to obtain a polyaniline / cotton composite fiber; S23: adding polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to deionized water to obtain a dispersion base solution, and adding graphene and carbon nanotubes to obtain a modified dispersion solution; immersing the polyaniline / cotton composite fiber in a glutaraldehyde solution for activation, taking it out, washing it, and immersing it in the modified dispersion solution to react and obtain a modified polyaniline / cotton composite fiber; S24: immersing the modified polyaniline / cotton composite fiber in a dodecylbenzene sulfonic acid solution to obtain a doped modified fiber; preparing a quaternary ammonium salt antistatic agent solution, adjusting the pH with acetic acid to obtain an antistatic impregnation solution, and immersing the doped modified fiber in the solution to obtain a conductive composite fiber.
6. The method for preparing a textile fabric according to claim 5, characterized in that: In S21: The solid-to-liquid ratio of the first pretreated cotton fiber to the hydrochloric acid solution is 1:(30-40); The concentration of the hydrochloric acid solution is 0.5-1M; The first pretreated cotton fiber is immersed in the hydrochloric acid solution for 10-15 minutes.
7. The method for preparing a textile fabric according to claim 5, characterized in that: In S22: The concentration of ammonium persulfate in the oxidant solution is 0.25-0.3M; The concentration of aniline monomer in the monomer solution is 0.2-0.25M; The solid-to-liquid ratio of the pretreated cotton fiber to the monomer solution is 1:(30-35); The molar ratio of the aniline monomer to ammonium persulfate is 1:(1-1.25).
8. The method for preparing a textile fabric according to claim 5, characterized in that: In S23: The mass fraction of the polyvinyl pyrrolidone is 0.8-1.2wt.%; The mass fraction of the sodium dodecylbenzene sulfonate is 0.2-0.5wt.%; The mass ratio of graphene to carbon nanotubes is (1-2):1; The concentration of the mixture of graphene and carbon nanotubes is 1.2-1.5 mg / mL; The mass fraction of the glutaraldehyde solution is 2-2.5wt.%; The solid-to-liquid ratio of the polyaniline / cotton composite fiber to the glutaraldehyde solution is 1:(25-30).
9. The method for preparing a textile fabric according to claim 5, characterized in that: In S24: The concentration of the dodecylbenzenesulfonic acid solution is 0.2-0.3M; The solid-liquid ratio of the modified polyaniline / cotton composite fiber to the dodecylbenzenesulfonic acid solution is 1:(35-40); The mass fraction of the quaternary ammonium salt antistatic agent solution is 0.8-1.2wt.%; The pH value is adjusted to 5.3-5.7 with acetic acid; The solid-liquid ratio of the doped modified fiber to the antistatic impregnation liquid is 1:(30-35).
10. A textile fabric prepared by the method for preparing a textile fabric according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method for self-assembling multifunctional poly-aniline / purified cotton composite conductive fabric
CN101403189A
Method for chemically plating silver on artificial fibers and textile
CN102733180A
Silver powder production method capable of controlling sintering activity
CN110899691A
Polyarmide fiber-imitated polyester fiber pantyhose
CN113774661A
Fiber complex and its use
CN1531608A
Cited By
Polyamide 6 high-conductivity fabric for textile-based electronic products and preparation method of polyamide 6 high-conductivity fabric
CN120311480A